ORCiM research festival: artistic experimentation in music: a dialogue on artistic research - Orpheus Instituut (Ghent, Belgium) (Gent Orpheus research centre in music, 2011)
A Dialogue on Artistic ResearchArtist-researchers from institutions around the world met in Ghent to share ideas, collaborate in musical experiences, exchange information and continue to develop their own views on the evolving field of Artistic Research in Music.DVDOn the occasion of ORCiMs third annual Research Festival in October 2011, artist-researchers from institutions around the world met in Ghent to share ideas, collaborate in musical experiences, exchange information and continue to develop their own views on the evolving field of Artistic Research in Music.This DVD captures the sounds, images and ideas that emerged from this rich gathering. It serves as an example of a new format ORCiM will use for its future outputs, a series of research outcomes that will aim to bridge the gap between academic publications and artistic products.In Artistic Research in Music, the perspective of the artist allows for the research questions to arise from the process of musical practice itself. Using Artistic Experimentation as a catalyst, researchers from the Orpheus Research Centre in Music [ORCiM] have engaged in research in-and-through musical practice, allowing them to develop new understanding and innovative methodologies that serve as an illustration of the field of Artistic Research and its potential future directions.